Kensiu Language Preservation : An Analysis Based on the Typological Framework of Language Threats - Nur Faaizah, Md Adam; Nur Farahkhanna, Mohd Rusli; Noor Saadah, Salleh; Wan Khairulhusna, Wan Mokhtar; Santrol, Abdullah; Ciptro, Handrianto (Brieflands, 2022)
The Kensiu Orang Asli community is a minority group in Malaysia with population about 208, living in Kampung Lubuk Legong, Kedah. The extinction of the indigenous language is a matter of great concern today. Therefore, a study on language preservation needs to be done so that the language of minorities can be saved from disappearing. The study aims to describe the preservation of the Kensiu language based on the framework of Language Threats Typology. It useda simple qualitative and statistical approachby using random sampling techniqueto select 150 respondents in Kampung Lubuk Legong, Baling, Kedah. The direct questionnaire techniques were used to obtain more accurate and have high reliability data. Data was analysed based on backgrounds and the demographics of the respondents. The results showed four factors that describe the preservation of the Kensiu language, namely gender, age group, parental ancestry, place of birth and language ability. Currently, the Kensiu language is also in a safe situation because 100% of the respondents say they are fluent in the Kensiu language. This study has contribution for policymakers in the country to do a perfect and orderly language planning to preserve the culture and language of Kensiu.